Maktub. - Coelho, Paulo ([London : Thorson : Harper Collins, 2024)
An essential companion to the inspirational classic 'The Alchemist', filled with timeless stories of reflection and rediscovery. From one of the greatest writers of our age comes a collection of stories and parables unlocking the mysteries of the human condition. Gathered from Paulo Coelho's daily column of the same name, Maktub, meaning 'it is written', invites seekers on a journey of faith, self-reflection, and transformation.
Keywords: Literature; Literature